Diferenciação e caracterização química de espécies de Phyllanthus utilizando técnicas hifenadas - Sprenger, Ricardo da Fontoura (Universidade Federal de São Carlos, 2016)
Several species of Phyllanthus genus are widely used in popular medicine, even though very few phytochemical reports on species such as: P. caroliniensis, P. stipulatus and P. tenellus are found in the literature. Furthermore, the official reference quality control methods, especially those related with authenticity assessment, are nonspecific for the species under analysis. Thereby, this work reports on the online chemical characterization of the ethanolic extract of six Phyllanthus species by liquid chromatography hyphenated to mass spectrometry (LC-MS) and liquid chromatography hyphenated to nuclear magnetic spectroscopy using automated solid phase extraction system, as interface (LC-SPE-NMR). The chapter 2 discusses the classification of commercial Phyllanthus samples acquired from different establishments in several Brazilian municipalities. The identification of various chemical markers from authentic samples of each species allowed the classification of commercial samples. The obtained results showed that they were misused, in spite of their labels nominating them as P. niruri, the majority of the tested samples were P. tenellus. None was classified as P. niruri. Chapter 3 discusses the use of statistical models for the chromatographic method development and also for the handling of MS data. Development of the method was carried out by experimental design furnishing chromatographic runs with short analysis time and high number of chromatographic bands. Statistical analysis using principal component analysis (PCA) allowed the unmistakable differentiation of species and pointed out to several of compounds responsible for this. Through the interpretation of the MS/MS data, using the mass analyzers QqToF and IT-MS, 22 compounds had their chemical structure elucidated, some of which have never been reported in the literature. Chapter 4 describes the results obtained by LC-SPE-NMR for the unequivocal structural elucidation of the secondary metabolites of the ethanolic extract of P. tenellus. The use of automated SPE interface facilitated the isolation of the compounds of interest, eliminating the need of using semi-preparative chromatography. The interpretation of NMR spectra enabled the identification of 9 compounds confirming the structures inferred by LC-MS.
Chemical differentiation of Phyllanthus species using hyphenated techniques
Keywords: Caracterização química; Cromatografia líquida acoplada a espectrometria de massas; Cromatografia líquida hifenada a ressonância magnética nuclear; Phyllanthus; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA